Lifestyle Modification in the Form of Diet and Physical Activity Proven Effective in Lowering Fasting Blood Sugar Levels of Pre-Diabetes Patients - Muh.Zukri Malik; I Kade wijaya; Muh.Taslim; Wanda; Atika Asri Putri (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Various diabetes prevention interventions vary in effectiveness including lifestyle modification interventions. This study aims to ascertain the effectiveness of lifestyle modification interventions in the form of diet and physical activity in lowering blood sugar levels in prediabetic patients. Quasi-Experimental Pre-Post Test Design with Control Group, the treatment group was given dietary and physical activity modifications in the form of counseling and close monitoring while the control group was not given intervention. 30 pre-diabetic patients with hyperglycemia aged between 18-65 years were selected to be sampled using simple random sampling technique. Data analysis using Wilcoxon test and independent sample t-test. The findings showed significant differences in GDP levels before and after the intervention (p<0.001). Lifestyle modification interventions in the form of diet and physical activity proved effective in lowering fasting blood sugar levels of pre-diabetic patients with an average decrease of 14.93 mg / dL. It is hoped that people can apply a healthy lifestyle, especially in processing food and exercising so as to avoid diabetes mellitus.